Avian influenza overview September–December 2024 - European Food Safety Authority, European Centre for Disease Prevention and Control; European Union Reference Laboratory for Avian Influenza; Leonidas Alexakis; Hubert Buczkowski; Mariette Ducatez; Alice Fusaro; Jose L. Gonzales; Thijs Kuiken; Karl Ståhl; Christoph Staubach; Olov Svartström; Calogero Terregino; et al. (EFSA Journal)
Abstract Between 21 September and 6 December 2024, 657 highly pathogenic avian influenza (HPAI) A(H5N1) and A(H5N5) virus detections were reported in domestic (341) and wild (316) birds across 27 countries in Europe. Many HPAI outbreaks in domestic birds were clustered in areas with high poultry density and characterised by secondary farm‐to‐farm spread. Waterfowl, particularly the mute swan, were primarily affected during this reporting period, with HPAI virus detections focused on south‐eastern Europe. Notably, A(H5N5) viruses expanded their geographic and host range, resulting in a surge in detections and mortality events described in gulls and crows. No new HPAI virus detections in mammals were reported in Europe during this reporting period, but the number of dairy cattle farms reportedly affected in the United States of America (USA) rose to >800 in 16 States, and HPAI virus was identified in two pigs in a mixed‐species farm. Between 21 September and 11 December 2024, 56 new human cases with avian influenza virus infection were reported from North America (45 A(H5N1) cases), Viet Nam (one A(H5)) and China (ten A(H9N2) cases). Most of the A(H5) human cases in North America (95.6%, n = 43/45) had reported exposure to poultry, live poultry markets, or dairy cattle prior to avian influenza virus detection or onset of illness. Human infections with avian influenza viruses remain rare and no evidence of human‐to‐human transmission has been documented in the reporting period. The risk of infection with currently circulating avian A(H5) influenza viruses of clade 2.3.4.4b in Europe remains low for the general public in the European Union/European Economic Area (EU/EEA). The risk of infection remains low‐to‐moderate for those occupationally or otherwise exposed to infected animals or contaminated environments.